Effectiveness of Setting Temperature on Moonfish Surimi Gel (Megalops cyprinoides) - Rosanti, Septri Amalia; Irawan , Irman; Zuraida, Ita; Diachanty, Seftylia; Pamungkas, Bagus Fajar (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Good characteristics of surimi can be seen from its ability to form a gel, one of which is the temperature setting. This study aims to determine the effectiveness of the setting temperature on the surimi gel of moonfish (Megalops cyprinoides). The study used a completely randomized design with treatments of five temperature setting with three replications. Parameters observed were gel strength, folding test, whiteness and expressible moisture content. The results showed that setting temperature had a significant effect on gel strength, folding test, whiteness degree and expressible moisture content (p<0.05) at 95% confidence level. The setting temperature treatment of 40oC and without setting had the highest gel strength compared to other treatments with the max load values ​​of 59.79 kg/cm2 and 60.63±1.44 kg/cm2, respectively, with a 5-fold test quality value, namely does not crack after being folded into quarters. The best setting temperature for the gel forming ability of fish surimi for moonfish is 40oC and without setting temperature.